Penyelesaian Sengketa Perbatasan Yang Ditinjau Melalui Implementasi Border Crossing Agreement Antara Indonesia-Filipina (Studi Kasus Pulau Miangas, Sulawesi Utara) - Sitti Navisah Muhidi (Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pasundan, 2019)
Attention to the brightest and outermost islands of Indonesia must be increased even more considering the cases of sipadan and ligits that Malaysia successfully claimed in 2002, similar things do not want to be done for other small islands such as islands in North Sulawesi Indonesia and directly adjacent to the Philippines. By using descriptive, qualitative study methods, the confidential information of cross-border agreements (borders of the Transboundary Agreement) between Indonesia and the Philippines, especially on the island of Miangas, is an example of a dispute that can be clarified through the legal certainty of international Albitration.